Comparative effectiveness of epilepsy surgery versus additional anti-seizure medications for Lennox–Gastaut syndrome: study protocol for a multicenter, mixed-methods study - Sandi Lam; Sandi Lam; Marc Rosenman; Marc Rosenman; Tracy Dixon-Salazar; Kelly G. Knupp; Liu Lin Thio; Taylor J. Abel; Taylor J. Abel; William P. Welch; William P. Welch; Laurel Reed; et al. (Frontiers in Neurology)
IntroductionLennox–Gastaut Syndrome (LGS) is a severe developmental epileptic encephalopathy without a known cure. Management of symptoms requires substantial care. Treatment options include anti-seizure medications, dietary therapy, and epilepsy surgery. Two main treatment pathways for patients with LGS with drug resistant epilepsy are additional anti-seizure medications or epilepsy surgery, which have been reported to be effective in reduction of seizure burden and improving quality of life. No studies have directly compared the outcomes of using epilepsy surgery versus using additional anti-seizure medications for the treatment of LGS.MethodsThis study is a multicenter, mixed-methods comparative effectiveness study of LGS patients who have undergone epilepsy surgery or have received an LGS-approved medication for treatment resistant seizures. Aim 1 will analyze the effect of surgical therapies and additional medication on two clinical outcomes: (1a) seizure-related healthcare utilization, and (1b) expressive communication, behavior, and parent-reported quality of life. Based on electronic health record review and coding validation as part of Aim 1a, we will develop computable phenotypes for LGS. The phenotypes will inform the analyses in Aim 1a and Aim 2. Aim 2 will describe the real-world utilization of these treatments across multiple healthcare institutions in the United States. Data will be collected from electronic health records, data marts in the National Patient-Centered Clinical Research Network (PCORnet®) format, caregiver surveys, and focus groups.DiscussionThis study of LGS will provide currently unavailable evidence concerning the real-world comparative effectiveness of epilepsy surgeries and additional anti-seizure medications. The outcomes are those that families identify as important: emergency medical care for seizures and patients’ functional outcomes. The results of this study may help guide decisions regarding the treatment of LGS and development of computable phenotypes for this rare disease. This study using PCORnet® data will also lay the groundwork for future large-scale studies on LGS and other rare epilepsies.Clinical trial registrationClinicalTrials.gov, identifier NCT05374824.